Improvement of Ultrasonically Welded Aluminum/Carbon Fiber Reinforced Polymer‐Joints by Surface Technology and High Resolution Analysis1. Issue 9 (3rd April 2013) - Balle, Frank; Emrich, Stefan; Wagner, Guntram; Eifler, Dietmar; Brodyanski, Alexander; Kopnarski, Michael
<x xml:space="preserve">Abstract</x> In order to achieve a more specific knowledge about the bonding mechanism of ultrasonically welded Al/CFRP‐joints, microscopic investigations were carried out. Transmission electron microscopy was used to investigate the interface between the aluminum and the CFRP sheet. One important result was the detection of mechanically deformed areas due to ultrasonic welding which lead to a reorientation of the crystal structure in surface near areas of mechanically pre‐treated aluminum. Furthermore it has been proven, that molten thermoplastic can penetrate into a cavernous, nanoscaled aluminum oxide layer, which was generated due to acidic etching of aluminum prior to ultrasonic welding. Because of the fact that hybrid joints with such chemically pre‐treated aluminum parts show most favorable strengths in comparative terms within single lap shear tests, there are clear indications, that in case of CF‐PA66 surface enlargement due to higher roughness is not the reason for this behavior. Instead of this, the sub‐microscopic interlocking of polymer and metal based on the generation of sub‐microscopic fine, porous, and open aluminum oxide structures is the key to improve the mechanical properties of ultrasonically welded Al/CFRP‐joints.